Experimental and Model-Based Analysis to Optimize Microalgal Biomass Productivity in a Pilot-Scale Tubular Photobioreactor - Weise, Tobias; Grewe, Claudia; Pfaff, Michael (Frontiers in Bioengineering and Biotechnology, 2020)
A dynamic coarse-grained model of microalgal growth considering light availability and temperature under discontinuous bioprocess operation was parameterised using experimental data from 15 batch cultivations of Nannochloropsis granulata in a pilot-scale tubular photobioreactor. The methodology applied consists of a consecutive two-step model parameter estimation using pooled, clustered and reorganised data to obtain initial estimates and multi-experiment fitting to obtain the final estimates, which are: maximum specific growth rate µmax = 1.56 d−1 , photon half-saturation constant KS,ph = 1.89 molph gX −1 d−1 , photon maintenance coefficient mph = 0.346 molph gX −1 d−1 and the cardinal temperatures Tmin = 2.3 ◦ C, Topt = 27.93 ◦ C and Tmax = 32.59 ◦ C. Biomass productivity prediction proved highly accurate, expressed by the mean absolute percent error MAPE = 7.2 %. Model-based numerical optimisation of biomass productivity for repeated discontinuous operation with respect to the process parameters cultivation cycle time, inoculation biomass concentration and temperature yielded productivity gains of up to 35 %. This optimisation points to best performance under continuous operation. The approach successfully applied here to small pilot-scale confirms an earlier one to lab-scale, indicating its transferability to larger scale tubular photobioreactors.